Systematic review of universal and targeted workplace interventions for depression. Issue 1 (26th October 2017) - Wan Mohd Yunus, Wan Mohd Azam; Musiat, Peter; Brown, June S L
Abstract : Depression is increasingly being recognised as a significant mental health problem in the workplace contributing to productivity loss and economic burden to organisations. This paper reviews recently published randomised controlled trials (RCTs) of universal and targeted interventions to reduce depression in the workplace. Studies were identified through searches of EMBASE, MEDLINE/PubMed, PsycINFO, PsycARTICLES Full Text, and Global Health and Social Policy and Practice databases. Studies were included if they included an RCT of a workplace intervention for employees targeting depression as the primary outcome. Twenty-two published RCTs investigating interventions utilising various therapeutic approaches were identified. The cognitive behavioural therapy (CBT) approach is the most frequently used in the workplace, while interventions that combine different therapeutic approaches showed the most promising results. A universal intervention in the workplace that combines CBT and coping flexibility recorded the highest effect size (d=1.45 at 4 months' follow-up). Most interventions were delivered in group format and showed low attrition rates compared with other delivery formats. Although all studies reviewed were RCTs, the quality of reporting is low. Interventions using different therapeutic approaches with different modes of delivery have been used. Most of these interventions were shown to reduce depression levels among employees in the workplace, particularly those that combine more than one therapeutic approaches.